Implementation of Cooperative Learning Model Type Fan-N-Pick Assisted by Picture Media to Improve Learning Outcomes of Fourth Grade Students at Kristen Nyama Elementary School - Likely, Frangky B; Rumtutuly, Fransheine; Septory, Jekriel (Honoli of Journal Primary Teacher Education, 2026)
The purpose of this study was to improve the learning outcomes of fourth-grade students of Nyama Christian Elementary School by implementing the Fan-N-Pick learning model assisted by image media. The research method used is classroom action research. The data collection process uses tests, observations and documentation. The improvement in student learning outcomes can be seen from the increase in the initial test, the overall average score was 54.06 while students who obtained scores reaching the KKM were 4 (25%), increasing in cycle I, namely the overall average score of students was 66.56 and students who obtained scores reaching the KKM were 10 (62.5%0. Student learning outcomes increased in cycle II with an overall average score of 79.37 and students who obtained scores reaching the KKM were 16 (100%). Thus, the application of the fan-n-pick learning model assisted by image media has a positive effect on learning in fourth-grade students of Nyama Christian Elementary School with the material of ethnic and cultural diversity.